The Role of Sana'a University Leadership in Activating the Quality Systems - Abdulgani Ahmed AL-Hawri; Ghalb .Hameed AL-Qanes (University of Science and Technology, Yemen, 2017)
The study aimed to detect the role of the Presidency of Sana'a University and the Deans of Colleges in activating the quality systems in colleges. The researchers used the descriptive approach and a questionnaire as a tool to achieve that aim. Results revealed that the role of Sana'a University leadership in  activating the quality systems was generally given poor assessment with regard to the questionnaire as a whole and to the five dimensions  (Planning for Quality, Quality awareness-raising, Establishment and Support, Implementation, Supervision and follow-up). In addition, there were no statistically significant differences between the participants'' responses that could be attributed to these variables: college, academic degrees and Years of Experience). Key words: Quality Systems, The role, University Leadership.